Pengaruh EPS, ROE dan DER terhadap Harga Saham Properti dan Real Estate yang Terdaftar di JII70 - Nilna Nikmatul Janaina; Deny Yudiantoro (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The property sector is one of the main sources for realizing investment, with the main sources coming from the industrial and housing sectors.the purpose of this study was to determine whether the variables EPS, ROE, and DER partially and simultaneosly affect the stock price variable. The study was conducted in property and real estate companies registered with JII70 for the period 2018-2020. The samples used were saturated samples taken from ten property and real estate. This research uses a type of quantitative approach. The data used is secondary data in the form of panel data obtained from the annual financial statements and closing stock prices of each company. The analysis method used is a regression analysis date panel eviews. The results showed partially that both EPS and DER variables had a positive effect on stock prices. While partially one variable that has no effect and negative to the stock price is ROE. Simultaneously the three variables EPS, ROE, dan DER have an effect on stock prices. Keywords: EPS; ROE; DER; stock price